2014
DOI: 10.1038/gene.2014.5
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in human CD1A is associated with susceptibility to tuberculosis

Abstract: CD1 proteins are antigen-presenting molecules that evolved to present lipids rather than peptides to T cells. However, unlike major histocompatibility complex genes, CD1 genes show low rates of polymorphism and have not been clearly associated with human disease. We report that an intronic polymorphism in CD1A (rs411089) is associated with susceptibility to tuberculosis in two cohorts of Vietnamese adults (combined cohort odds ratio 1.78; 95%CI: 1.24-2.57; p=0.001). These data strengthen the hypothesis that CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 14 publications
(15 reference statements)
2
27
0
Order By: Relevance
“…These data highlight the need to understand the distinct functions of CD1a, CD1b, and CD1c. Though CD1 proteins exhibit limited structural variation, a polymorphism in CD1a that is associated with low surface expression and T-cell activation was shown to be associated with TB [55], [56]. CD1b is expressed in TB granulomas and may locally activate lipid reactive T-cells [57].…”
Section: Mycobacterial Antigen Presentation By Cd1mentioning
confidence: 99%
“…These data highlight the need to understand the distinct functions of CD1a, CD1b, and CD1c. Though CD1 proteins exhibit limited structural variation, a polymorphism in CD1a that is associated with low surface expression and T-cell activation was shown to be associated with TB [55], [56]. CD1b is expressed in TB granulomas and may locally activate lipid reactive T-cells [57].…”
Section: Mycobacterial Antigen Presentation By Cd1mentioning
confidence: 99%
“…Group 1 CD1 T cell responses correlate with mycobacterial load such that patients with active tuberculosis had higher frequencies of mycolic acid specific T cells (producing IL-2 and/or IFN-γ) than those subjects who had been treated for tuberculosis, although with substantial despite variability among patients (54). Although they have limited genetic variation, polymorphisms in CD1a are associated with susceptibility to M. tuberculosis infection (55). Nonetheless, the conserved conformation of the CD1 proteins makes CD1-restricted T cells an attractive target for vaccines and lipid based vaccination trials have shown partial protection in a highly susceptible animal model (56).…”
Section: Conventional Cd8 T Cells Unconventional Cd8 T Cells and Unimentioning
confidence: 99%
“…It is difficult to imagine that human populations have such sequence variation, but humans and chimpanzees share the same sequence in the α1 and α2 domains of the MR1 protein. In regard to CD1 genes, SNPs in the α1 domain (104, 105) and the non-coding regions (106) of the human CD1a and CD1d genes have been identified, and non-synonymous mutations have also been deduced from exon 2 of both genes (107). Few identified SNPs support that MR1 and CD1 genes are still very conserved and appear similar to innate immune receptors such as TLRs in terms of sequence stability in human populations.…”
Section: Highly Conserved Antigen-presenting Moleculesmentioning
confidence: 99%